Effect of coating treatment (Protector®) application on quality of mango during storage - Kamalaldin, Nurulain Amirah (2015)
Mango fruit usually has a short storage life to maintain its fruit quality during storage period, which is only about two to three weeks at 10-13°C. Decay is one of the most important causes of postharvest losses in mango. Thus, the objective of this study was to determine the effectiveness of Protector®, a new chemical found in the market that claimed to be able to maintain quality of agriculture produce treatment on storage life of ‘Chokanan’ mango fruits. In order to prolong the storage life of the ‘Chokanan’ mango, the fruit were dipped in four different concentrations of Protector® diluted with distilled water (10ml: 1000ml, 10ml: 2000ml, 10ml: 3000ml and 10ml: 4000ml) before storage in cool room 10-13°C.‘Chokanan’ mango fruit were treated with sodium hypochlorite before they were coated. Fruit were then analyzed after 28 days of storage for weight loss, pulp firmness (N), peel colour, percentage of disease incidence and diseases severity, titratable acidity, vitamin C, pH and soluble solid concentration. The application of different concentration of Protector® on mango fruit did showed significant effects on some storage qualities. Further studies are required in enhancing the effectiveness of this coating treatment in maintaining the quality of mango fruit working with a better ranges of concentrations.